New neurons in the adult striatum: from rodents to humans. Issue 9 (September 2015) - Inta, Dragos; Cameron, Heather A.; Gass, Peter
Highlights Recently, adult neurogenesis was shown to occur in the normal human striatum. Similar newborn-specific striatal interneurons were described in different species. Adult-generated striatal neurons may derive from the pallium/subventricular zone. Adult striatal neurogenesis could be of relevance for neuropsychiatric disorders.